Prospective long-term follow-up analysis of the cardiovascular system in marathon runners: study design of the Pro-MagIC study. Issue 1 (19th July 2020) - Schoenfeld, Julia; Schindler, Michael Johannes; Haller, Bernhard; Holdenrieder, Stefan; Nieman, David Christopher; Halle, Martin; La Gerche, André; Scherr, Johannes
Abstract : Introduction: Prolonged strenuous exercise training may result in structural, functional and electrical cardiac remodelling, as well as vascular and myocardial injuries. However, the extent to which high-volume, intense exercise is associated with arrhythmias, myocardial fibrosis, coronary heart disease and pathological alterations of the vasculature remains unknown. In addition, there is no clear consensus on the clinical significance of these exercise-induced changes. Previous studies typically used cross-sectional designs and examined exercise-induced cardiovascular changes in small cohorts of athletes for up to 3–7 days of recovery. Long-term longitudinal studies investigating cardiovascular changes induced by prolonged strenuous exercise in large cohorts of athletes are needed to improve scientific understanding in this area. Methods and analysis: In this prospective observational monocenter study, 277 participants of the Beer, Marathon, Genetics, Inflammation and the Cardiovascular System (Be-MaGIC) study (ClinicalTrials.gov: NCT00933218 ) will be invited to participate in this 10-year follow-up study. A minimum target sample size of 130 participants will be included in the study. Participating athletes will be examined via the following: anthropometry, resting electrocardiography and echocardiography, blood sampling, retinal vessel diameters, carotid sonography and cardiopulmonary exercise testing, including exercise electrocardiography. Discussion: This longitudinal study will provide comprehensive data on physiological changes in the cardiovascular system and the development of pathologies after a 10-year period of prolonged and strenuous endurance exercise. Since the participants will have engaged in a wide range of training loads and competitive race events, this study will provide useful risk factor determinants and training load cut-off values. The primary endpoint is the association between the exercise-induced increase in cardiac troponin during the Munich marathon 2009 and the decline in right ventricular ejection fraction over the next 10 years. Trial registration number: NCT04166903 .